The Relationship between Stability and Ion Conduction of Trivalent Cation Doped Ceria - Akram La Kilo; Kusrini Kusrini; Deasy Natalia Botutihe (Jambura Journal of Chemistry, 2021)
This research aims to study the stability of CeO2 structure which doped with trivalent oxide which become Ce1-xMxO2- ( M= Lu3+, Yb3+, Er3+, Y3+, Gd3+, Eu3+, Sm3+, dan La3+) compound through atomistic simulation, the value of x present the concentration number of the substitution dopant of Ce4+ partially and the concentration of the dopant is limited to 10%. This research is explorative theoretical using methods of computational chemistry by atomistic simulating using GULP. The objects in this study was 8 trivalent oxide with the short-range potential as the input data. Potential short-range used in this study is the Buckingham potential. The results of geometry optimization at a constant pressure showed the differences between cell parameters of doped CeO2 before and after the atomistic simulation corresponds with the experimental results is only 0.02%. The results showed that the stability of doped CeO2 structure is decreased with increasing concentrations of dopants. A decrease int he stability of CeO2 doped with Lu, Ce, Er, Gd, Eu, Nd and La is greater than the decrease in the stability of CeO2 doped with Sm, Y and Yb.